Potential for elimination of SAR‐CoV‐2 through vaccination as inspired by elimination of multiple influenza viruses through natural pandemics or mass vaccination - Chen, Ji‐Ming; Sun, Ying‐Xue; Chen, Ji‐Wang (Journal of medical virology, 2020)
The ongoing pandemic of coronavirus disease 2019 (COVID‐19) caused by the novel virus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has claimed many lives worldwide. To combat the pandemic, multiple types of vaccines are under development with unprecedented rapidity. Theoretically, future vaccination against COVID‐19 may fall into long‐term costly guerrilla warfare between SARS‐CoV‐2 and humans. Elimination of SARS‐CoV‐2 through vaccination to avoid the potential long‐term costly guerrilla warfare, if possible, is highly desired and worth intensive consideration. Human influenza pandemics emerging in 1957, 1968, and 2009 established strong global herd immunity and led to the elimination of three human influenza viruses, which circulated worldwide for years before the pandemics. Moreover, both clade 7.2 of subtype H5 highly pathogenic avian influenza virus and subtype H7N9 avian influenza virus circulated in poultry in China for years, and they have been virtually eliminated through mass vaccination in recent years. These facts suggest that the rapid establishment of global herd immunity through mass vaccination using an appropriate vaccine could eliminate SARS‐CoV‐2. The coming 2 years are a golden time for elimination through vaccination, which requires tremendous national and international collaboration. This review also prioritizes the efficacy of vaccines for COVID‐19 and elucidates the importance of the development of more live vaccines for COVID‐19. Highlights Future vaccination against coronavirus disease 2019 (COVID‐19) may fall into long‐term costly guerrilla warfare between severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and humans. Elimination of SARS‐CoV‐2 through vaccination is highly desired and worth intensive consideration. Multiple influenza viruses have been eliminated through natural pandemics or mass vaccination. The coming 2 years are a golden time for the elimination of SARS‐CoV‐2 through mass vaccination. Rapid establishment of global herd immunity through vaccination using a live vaccine could eliminate SARS‐CoV‐2.